Perception of the health of children living and working on the streets of Sunnyside - Part 1: Literature review and methodology - L Prinsloo (AOSIS, 2003)
The phenomenon of street children is generating increasing concern in South Africa. The number of street children has grown because of the current economic hardship in South Africa, increasing levels of violence and widespread family and community disruption.